2007
DOI: 10.1007/s00248-006-9159-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exogenous Triiodothyronine (T3) on Fecal Shedding of Escherichia coli O157 in Cattle

Abstract: Fecal prevalence of Escherichia coli O157 in ruminants is highest in the summer months and decreases to low or undetectable levels in the winter. We hypothesize that the seasonal variation of this pathogen is a result of physiological responses within the host animal to changing day length. The thyroid is an endocrine gland known to respond to changing day length. Two experiments were conducted to determine if a hyperthyroid status would initiate fecal shedding of E. coli O157 in cattle during the winter when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Our data indicated that hormones known to respond to day length (melatonin, tri-iodo-thryonine, thyroxine) were involved in the population dynamics and subsequent fecal shedding of E. coli O157:H7 in cattle [6, 7]. …”
Section: Resultsmentioning
confidence: 99%
“…Our data indicated that hormones known to respond to day length (melatonin, tri-iodo-thryonine, thyroxine) were involved in the population dynamics and subsequent fecal shedding of E. coli O157:H7 in cattle [6, 7]. …”
Section: Resultsmentioning
confidence: 99%
“…In evaluating which hormones (known to respond to changing da y-length) to examine, melatonin based on the secretion patterns that are inverse to E. co/i 0157:117 shedding patterns, stands out as a logical choice. However, a number of hormones offer intriguing possibilities, some of which we have demonstrated can also influence fecal shedding of E. colt 0157:1-17 (Edrington of al., 2007). The most probable scenario likely involves multiple hormones, or other compounds yet to he discovered, functioning in a cascade of events to influence i-:.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known what climate-associated factors contribute to peak summer prevalence of EHEC; a hypothesis that day length impacts bovine hormones was tested by exposing cattle to additional 5 h of artificial lighting=day, and increased prevalence of EC O157:H7 was observed, compared to controls; 43 days after cessation of lighting, prevalence decreased to control levels (Edrington et al, 2006), and cattle treated with exogenous thyroid hormone shed the same numbers of EC O157 as controls in winter, and marginally less in summer (Edrington et al, 2007). Acyl-homoserine-lactone (AHL) autoinducer produced by non-EHEC appear to enhance EHEC colonization of the bovine GIT, and the rumen samples from feedlot cattle were negative for AHLs in the winter .…”
Section: Seasonal Prevalencementioning
confidence: 99%